Legal limitations to Brazilian university autonomy - Galizia, Fernando Stanzione; Azevedo, Maria Antonia Ramos de [UNESP]; Arruda, Rodrigo Sinigaglia [UNESP] (Univ Republica, Comision Sectorial Ensenanza, 2023)
The text analyzes, from the legal, political, and social perspectives, the concept of university autonomy that currently supports Brazilian universities. After that, it reflects on the reasons why this autonomy is not implemented in practice, with special attention to the government's role in this process. Finally, it discusses proposals for changes in university autonomy that seek to change this scenario and allow universities to actually use all the autonomies guaranteed by the Brazilian law. In the final considerations, it emphasizes the importance of the concept of autonomy for universities to play their strategic role in building the Brazilian nation and the importance of a true rescue of these institutions by the new federal government.
Keywords: higher education; university autonomy; university policy; university management; university institutional organization